Stakeholder perceptions of sustainability reporting on the websites of technical universities in Ghana - Yankey, N.; Amaning, N.; Akwaa-Sekyi, E.K.; Marfo, E.O.; Amoako, K.O. (Websites of technical universities in Ghana, 2022)
Purpose – This paper explores stakeholder perceptions on the nature and extent of sustainability reporting on the websites of technical universities (TUs) in Ghana. Design/methodology/approach – The authors collected data from the websites of the 10 TUs in Ghana and interviewed the stakeholders of the TUs. In analyzing the data, the authors used thematic analysis for the interview responses. The authors also adopted the global reporting initiative (GRI) guidelines and campus sustainability assessment tools for the presentation and analysis of the sustainability disclosures on the websites of the TUs. Findings – The authors found that due to weak institutional coercions, there were limited disclosures on the websites of the TUs, which aimed at gaining stakeholders’ legitimacy; the disclosures were more focused on organizational profile, governance and educational aspects of sustainability. To a large extent, while some external stakeholders such as parents, regulators and alumni appear to be less interested in the disclosures on the TU’s websites, internal stakeholders such as employees (teaching and non-teaching staff) and students who frequently visited the TU’s websites perceived limited reporting and were not impressed with the extent of sustainability disclosures on these websites. Practical implications – The findings of this study are intended to assist policy-makers in the educational sector to appreciate the importance of sustainability reporting on their websites. The results of this study will assist higher educational institutions (HEIs) in increasing the success rate of sustainability implementation by overcoming the lack of sustainability disclosures on their websites. Thus, the results of this study have implications for sustainability implementations, particularly those in emerging economies and policy-makers of universities worldwide. Originality/value – This study could provide two significant values. First, to the best of the authors’ knowledge, no other study has explored stakeholder perceptions of sustainability reporting in implementing sustainability within the education sector. Second, the results were arrived at by combining stakeholder consultations with content analyses, which could be a good guideline for sustainability implementation in the educational sector of developing countries
Research Article
Keywords: Institutional theory; Ghana; Websites; Sustainability reporting; Global reporting initiative; Technical universities